An Experimental Approach to Sensors Silicon Forced - prasad Tripathy, Hara; Pattanaik, Priyabrata; Kumar Kamilla, Susanta (International Journal of Psychosocial Rehabilitation, 2019)
According to this literature, a silicon forced sensors is offered by which the measurement of the force is calculated by means of force exerted on the gauge made up of polysilicon. Particular gauge is stressed by a metallic plate on which the maximum force of 500 kN is applied. The total force is calibrated with the change in resistance. Our model is constructed for the temperature change and the plane sketching and the bending of the stresses into the chip. Piezo-resistive module made up of the “Comsol Multiphysics 4.3” is employed for the simulation purposes.